Effect of temperature on mechanical energy absorption of graphene-based honeycomb structure doped boron and nitrogen - Nguyen, Minh Son; Nguyen, Hoang Linh; Tran, The Quang; Vuong, Van Thanh; Do, Van Truong (JST: Engineering And Technology For Sustainable Development, 2023)
Numerous applications require the use of energy absorption materials (EAM), such as helmets and bulletproof vests. Graphene-based carbon honeycombs (GCHs) are a special type of EAM that have garnered significant attention from scientists due to their mechanical energy absorption capacity, which can reach up to 5440MJ/m3, as well as their high stability under high temperatures. GCHs have shown great potential as mechanical energy absorbers. However, there have been few studies on honeycomb structures made from monolayer C3B, C3N, and NB, which also have mechanical potential similar to graphene. This study focuses on investigating the energy absorption capacity of C3B, C3N, and NB-based honeycomb structures (GBNHs). The study found that GBNHs have an energy absorption capacity of over 5500MJ/m3 and an anti-penetration ability exceeding 9000MJ/m3. These results provide insight into the potential for using GBNHs as a novel and promising EAM in the future.